Exploring the prebiotic activity of edible insect flour: a sustainable functional food ingredient - Foti, Paola; Sanfilippo, Rosamaria R.; Romeo, Flora V. (Frontiers in Industrial Microbiology, 2025)
Edible insect flour, particularly from house cricket (Acheta domesticus) and mealworms (Tenebrio molitor), is gaining attention as a sustainable and functional food ingredient due to its high nutritional value and low environmental impact. The edible insects are considered a source of micronutrients and protein which play a crucial role as they are involved in several physiological processes. Moreover, edible insects are also a source of fatty acids and fiber. Beyond these recognized benefits, insect flour may also contribute to gut health through potential prebiotic properties. Indeed, several studies highlighted that insect flour may interact with probiotic bacteria by modulating their metabolism. In the gut microbiota, Lactobacillus and Bifidobacterium, the most important genera for their probiotic activities are known to be susceptible to the action of prebiotics. However, further study is needed on the strain-dependent response of probiotics to insect flour. These highlighted activities related to the application of insect flour as food and feed, underline its functional value beyond its nutritional content, suggesting it as a new ingredient capable of promoting beneficial gut microbiota.